Radio frequency identification (RFID) range test for animal activity monitoring - Mohd Hafiz, Yusoff@Che Abdullah; Azrul Amri, Jamal; Engku Fadzli Hasan, Syed Abdullah; Azmi, N.; Kamarudin, L.M.; Zakaria, A.; A/L Kanagaraj, E; Badlishah Ahmad, R. (2019)
Object tracking is an important application in which applicable in many areas, included but not limited to tracking the items in shopping malls, or instrument tracking in factories/industrial areas. The application of Radio Frequency Identification (RFID) for object tracking has expanded not to only object tracking but also cover human monitoring (e.g. workers monitoring, marathon monitoring) and livestock monitoring. Advantages of using RFID compared to other wireless technologies for monitoring applications is that multiple objects can be detected simultaneously. The aim of this paper is to characterize the RFID readability in relation to operational factors, orientation and range. The outcome of this research is useful as a reference for future works. This study will provide a feasibility study on the use of Ultra High Frequency (UHF) solutions for future studies focusing on animal tracking. This work used ThingMagic M6e RFID reader from JADAK as the RFID reader and the maximum detection range for different RFID tags were identified. In addition, this work also investigates different GEN-2 setting such as Tari. Despite using the commercialized tags, this study was conducted to investigate the characteristic of the tags in the real-deployment environment (for goat monitoring). The eating behaviour of each goat is then monitored through the Received Signal Strength Indicator (RSSI) between tag and reader